Comparative Valuation of an ICT Firm Using Discounted Cash Flow and EV/EBITDA Multiples — Evidence from PT ESA - Kamal Abdillah; Nurul Aisyah Rachmawati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2026)
This study analyzes the firm valuation of PT Elang Strategi Adidaya (PT ESA), an Indonesian ICT system integrator experiencing rapid revenue and profit growth alongside persistent operating cash flow constraints. Despite strong financial performance, liquidity pressure arises from a high proportion of indirect projects with long payment cycles, highlighting the need for an appropriate valuation approach to support investment decisions. Using a qualitative case study method, this research combines financial statement analysis with in-depth interviews of key management and operational stakeholders. Firm valuation is conducted using Book Value, Discounted Cash Flow (DCF) with Free Cash Flow to Firm (FCFF), and relative valuation through EV/EBITDA multiples based on comparable ICT firms. The results show that PT ESA’s book value of IDR 37.75 billion represents a conservative lower bound and does not reflect future cash flow potential or intangible assets. In contrast, the DCF approach estimates an enterprise value of approximately IDR 609.07 billion, supported by strong growth prospects and profitability. The EV/EBITDA analysis further indicates valuation upside relative to industry peers. Overall, cash flow–based valuation provides a more representative measure of firm value for high-growth ICT companies facing working capital challenges.